Clean technology and the environment: Key issues and implications in belt and road initiative economies - Nanli, Zhu; Xiaoping, Li; Sohail Akhtar, Muhammad; Bilal, Ahmer (Frontiers in Environmental Science, 2022)
Belt and Road initiative has been planned by China to start the collaboration among relevant economies in the sector of technology innovation. The study examines the impact of technology innovation on environmental quality among the host economics of one Belt and Road initiative (BRI) by using panel data of 45 economies from 1991-2019. The study employs a panel fully modified ordinary least squares (FMOLS) to estimate the long-run association among suggested variables. The outcomes validate a healthy cross-sectional dependence within the panel OBRI economies. An estimated result of FMOLS specifies that an increase in patent and trademark improves the quality of the environment in only Europe in the long-run, while trademark also improves the environment in OBRI, MENA, and Central Asia. In short-run, panel heterogeneous causality approves the bi-directional causality among patent, trademark, and CO2 emission. The study stressed to articulate environment-friendly policies in technology innovation in OBRI regions.